Pemerolehan Bahasa Anak Usia Satu Sampai Tiga Tahun Desa Bangun Rejo Kabupaten Kutai Kartanegara - Dewi, Rijafi Sukma; Sulistyowati, Endang Dwi; Elyana, Kukuh (Universitas Mulawarman, 2020)
This reseach discusses the language acquisition of children aged one to three years in terms of phonological and syntactic acquisition. This study aims to describe the stage of language acquisition for children aged one to three years in phonological and syntactic aspects in Bangun Rejo village, Tenggarong Seberang District. Systematic, factual, and accurate. The collection techniques used were observation techniques, interview techniques, and note-taking techniques.Data analisys techniques used by researchers are data reduction techniques, data presentation, and drawing conclusions. The result of reseach on the phonological aspect show that children aged one to three years are able to pronounce vowel sounds [a], [i], [u], [e] and [o]. The consonants that can be pronounced range from seven to fourteen consonants. However, at this age period, children have not been able topronounce the consonant [r] and the pronounciation tends to be replaced by the consonant [l],[w], and [y].In the syntactic aspect, children aged one to three years are gradually able to pronounce one-word utterances, and a series of words which are then formed into declarative, interrogative, and imperative sentences.